Problems of Translating Navoy's Lyrics into Foreign Languages: Masalah Terjemahan Lirik Navoi ke dalam Bahasa Asing - Shermamatova Shermamatova (Academia Open, 2024)
This article critically examines the translations of Alisher Navoi's ghazals and rubai into English by both Uzbek and foreign translators. The study employs a rigorous analysis to evaluate the achievements and shortcomings of these translations. Methodologically, it employs a comparative approach to highlight variations in linguistic nuances and cultural interpretations. The results shed light on the diverse approaches taken by translators, offering insights into the challenges faced and suggesting improvements for future endeavors. The implications of this research extend to the broader field of literary translation, emphasizing the importance of preserving the cultural and linguistic richness of Navoi's poetry in English renditions. Highlights: Cross-cultural Examination: This study conducts a comprehensive analysis of Alisher Navoi's poetry translations into English by both Uzbek and foreign translators, emphasizing the cultural nuances embedded in the process. Translator Strategies: The article highlights diverse translation approaches, evaluating the achievements and shortcomings of English renditions of Navoi's ghazals and rubai, providing valuable insights for future translation endeavors. Preserving Literary Richness: Through a comparative method, the research underscores the importance of maintaining the cultural and linguistic richness of Navoi's poetry in English translations, contributing to the broader field of literary translation studies. Keywords: Bilingual Dictionary, Translation, Ghazals, Rubai, Word Choice